2014
DOI: 10.1016/j.sna.2014.02.030
|View full text |Cite
|
Sign up to set email alerts
|

AlAl thermocompression bonding for wafer-level MEMS sealing

Abstract: Al-Al thermocompression bonding has been studied using test structures relevant for wafer level sealing of MEMS devices. Si wafers with protruding frame structures were bonded to planar Si wafers, both covered with a sputtered Al film of 1 µm thickness. The varied bonding process variables were the bonding temperature (400 °C, 450 °C and 550 °C) and the bonding force (18, 36 and 60 kN). Frame widths 100 µm, 200 µm, with rounded or sharp frame corners were used. After bonding, laminates were diced into single c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 8 publications
(14 reference statements)
3
24
0
Order By: Relevance
“…Similar temperature and pressure dependences are observed when Sn layers are placed on Al surface and between Al layers; therefore, as long as Sn exists inside Al, high‐yield long‐standing vacuum sealing is achieved in Al‐Al bonding at 400 °C and lower, even though Al surface has been exposed to atmosphere. On the other hand, when no Sn exists in bonding layer, vacuum sealing cannot be achieved in Al‐Al bonding below 400 °C, which agrees with previous reports on conventional Al‐Al bonding .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Similar temperature and pressure dependences are observed when Sn layers are placed on Al surface and between Al layers; therefore, as long as Sn exists inside Al, high‐yield long‐standing vacuum sealing is achieved in Al‐Al bonding at 400 °C and lower, even though Al surface has been exposed to atmosphere. On the other hand, when no Sn exists in bonding layer, vacuum sealing cannot be achieved in Al‐Al bonding below 400 °C, which agrees with previous reports on conventional Al‐Al bonding .…”
Section: Resultssupporting
confidence: 90%
“…(2) as can be seen from Al-Sn binary phase diagram in Fig. 3 [7], eutectic reaction in Al-Sn system occurs at Sn concentration of 97.6 at% and temperature of 228°C, and no intermetallic compounds exist in entire phase space, so that Al parts can easily come into contact with each other via liquid phase with near-liquidus composition in thermocompression bonding process, and Al interdiffusion can be expected on the contact surface; (3) oxidation rate of Sn in atmosphere at room temperature is slow, and the thickness of oxide film is below 10 nm after 100 h [8]; (4) and Sn vapor pressure at 400°C is as low as about 10 −12 Pa [9], and has no effect on vacuum sealing. The reason behind choosing Mg as an additive element is that when 0.3 wt% Mg to 5 wt% Mg is added in high vacuum bonding of Al at 450°C and higher, products of reaction between Al 2 O 3 and Mg are formed and coagulate; this results in destruction of the surface oxide film so that exposed Al area expands, thus contributing to a firm bonding.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…[17][18][19] It was found that Al films sputtered on SiO2 can be bonded at lower temperatures than those sputtered directly on Si wafers. 18 We also found that higher quality bonding in terms of dicing yield and bond strength can be achieved by increasing the bonding temperature and/or bond force.…”
mentioning
confidence: 99%
“…18 We also found that higher quality bonding in terms of dicing yield and bond strength can be achieved by increasing the bonding temperature and/or bond force. 17 In the current work, we use transmission electron microscopy (TEM) to investigate bonded interfaces realized with Al deposited on Si or on SiO2 to explore possible reasons leading to differences in dicing yield. The impact of increasing the bond force and bond temperature on the resulting bond interface is also investigated.…”
mentioning
confidence: 99%
“…As a calculation shows (4), the elastic energy is too low to influence the bonding between atoms directly, but the applied stress and the resulting strain breaks up the surface layer. The wafers are bonded at high temperatures, usually in the range of 400°C to 550°C (1)(2)(3)(5)(6)(7). In recent experiments, Malik et al were able to reduce the required bonding temperature to about 300°C by depositing the Al metallization layer onto an intermediate SiO2 layer (3).…”
Section: Introductionmentioning
confidence: 99%